A Study on Electro-dynamic Brake Control Strategy of Hydrogen-powered Autonomous-rail Rapid Tram - LUO Xiaofeng; XIAO Lei; PENG Jing; FU Jianchao; WANG Hao; HUANG Dayang; LU Jun (Kongzhi Yu Xinxi Jishu)
The electro-dynamic braking capacity of hydrogen-powered autonomous-rail rapid tram is severely limited by the state of charge (SOC) of the energy storage battery and the operational status of the hydrogen fuel cell. When the energy storage battery is near its full charge state and the hydrogen fuel cell continues to generate power, the storage battery is unable to store the electrical energy generated from electro-dynamic braking, leading to the failure of the electro-dynamic braking function. To maximize the electro-dynamic braking capacity of hydrogen-powered autonomous-rail rapid trams, this paper proposes an electro-dynamic braking control strategy based on pedal deceleration demand. It firstly calculates the total vehicle electro-dynamic braking force based on brake pedal stroke and load status. It then combines the current energy status of the storage system and the hydrogen fuel cell system to initiate a brake torque request to the traction system. It also calculates the electro-dynamic braking force corresponding to the deceleration required by the brake pedal stroke, optimizing the output of electro-dynamic braking force under different load, intermediate gear placement, and medium-low speed conditions. The test results show that with this electro-dynamic braking control strategy, the train fully exploits its electro-dynamic braking capacity under medium-low gear placement and medium-low speed working conditions in AW0 circumstances. It meets the design requirements for regenerative braking energy recovery of hydrogen-powered autonomous-rail rapid tram under the current electro-dynamic braking system architecture.